PENGARUH MODEL TGT BERBANTUAN MEDIA TTS TERHADAP HASIL BELAJAR SISWA PADA MATERI TATA NAMA SENYAWA - Rengen, Yunita Ellysa; Sahputra, Rachmat; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research aimed to know the differences of students’ learning result and the influence of cooperative learning model type TGT using Media TTS on the material of compound nomenclature at class X SMA Koperasi Pontianak. The form of research was quasi experimental with control group design pre-test and post-test design. The tool of data collection was taken from students’ test used essay. The population in this research is all of students at class X SMA Koperasi Pontianak. In collecting the sample the researcher used sampling saturated technique. Experiment class and control class were determinate used random sampling and determinable that class XA as an experiment class and class XB as a control class. The result of pre-test by using t-independent test showed that there is no differences in students' ability of experiment class and control class. But, the result of post-test using t-independent test the researcher found that there is the differences result between experiment class students and control class students after they got treatment that have been given before. The result of effect size was 1,34 which mean that the cooperative learning model type TGT used media TTS gave an influence 40,99% in improving students’ learning result. Kata Kunci : Teams Games Tournament (TGT), Crossword (TTS), Compound                         Nomenclature, Learning Outcomes